Abandoned Tracks : The Underground Railroad in Washington County, Pennsylvania - Mainwaring, W. Thomas, 1952- (Book collections on Project MUSE., 2018)
"This book incorporates elements of antebellum history, Underground Railroad studies, and folklore history. Washington County, PA is located at the border of Pennsylvania, Ohio, and West Virginia, and so proved to be a key junction in the 19th century Underground Railroad. Mainwaring goes in depth to separate legends and truth of the actual story of the Railroad in this region, and simultaneously demonstrates how difficult it is to distinguish between fact and fiction. Emotion, memory, family myths, and wishful thinking all combine to obscure the reality of the Underground Railroad, both here and elsewhere in the US."--Provided by publisher.